Evaluation of Hepatic Toxicity after Repeated Stereotactic Body Radiation Therapy for Recurrent Hepatocellular Carcinoma using Deformable Image Registration. Issue 1 (December 2018) - Lee, Sumin; Kim, Hojin; Ji, Yunseo; Cho, Byungchul; Kim, Su; Jung, Jinhong; Kwak, Jungwon; Park, Jin-hong; Lee, Sang-wook; Kim, Jong; Yoon, Sang
Abstract This study aimed to evaluate hepatic toxicity after repeated stereotactic body radiation therapy (SBRT) for recurrent hepatocellular carcinoma (HCC) using deformable image registration (DIR). Between January 2007 and December 2015, 85 patients who underwent two sessions of SBRT for HCC treatment were retrospectively analyzed. A DIR technique was used to calculate the cumulative dose of the first and second SBRT to the normal liver by matching two computed tomography simulation images. The Dice similarity coefficient (DSC) index was calculated to evaluate DIR accuracy. Before the first and second SBRT, 6 (7.1%) and 12 (14.1%) patients were Child-Pugh class B, respectively. Median tumor size was 1.7 cm before both SBRT treatments. Mean DSC index value was 0.93, being >0.9 in 79 (92.9%) registrations. Median cumulative mean liver dose (MLD) was 9.3 Gy (interquartile range, 7.6–11.7). Radiation-induced liver disease developed in three patients, and two of them, with Child-Pugh class B, experienced irreversible liver function deterioration following the second SBRT. The DIR method provided reliable information regarding cumulative doses to the liver. In patients with Child-Pugh class A liver function, repeated SBRT for small recurrent HCC could be safely performed with acceptable hepatic toxicity.